Pachinko - Lee, Min Jin (London : Apollo, 2017)
A victorian epic transplanted to Japan, following a Korean family of immigrants through eight decades and four generations.
Fiction
ENH
Keywords: Families -- Korea -- Fiction; English literature; Koreans -- Japan -- Fiction